Peptide‐assisted supramolecular polymerization of the anionic porphyrin meso‐tetra(4‐sulfonatophenyl)porphine. Issue 6 (14th June 2022) - Kohn, Eric M.; Shirley, David J.; Hinds, Nicole M.; Fry, H. Christopher; Caputo, Gregory A.
Abstract: Electronics made from biological materials are desirable for use in medical devices, biosensors, and soft robotics because they have properties inaccessible to current inorganic technologies. Here, a series of cationic peptides were developed to self‐assemble with the anionic porphyrin meso‐tetra(4‐sulfonatophenyl)porphine (TPPS4 ) into supramolecular light‐harvesting wires known as J‐aggregates were developed. In addition to quantifying the binding events between each peptide and TPPS4, we found co‐incubation with mixed peptides allowed TPPS4 to bridge two different peptides at their terminal porphyrin‐binding regions. The J‐aggregates formed on macroscopic scale in near quantitative yield within ~3 h and readily interconverted with the soluble monomers upon cycling the pH; to our knowledge, this is the first report of a peptide‐porphyrin system with such properties. This work has practical and conceptual relevance to the development of new bioelectronic materials. Abstract :